Historical and contemporary genotypic population structure of pea Ascochyta blight pathogens Ascochyta pinodes and Phoma pinodella. - Furgał-Węgrzycka, Helena (Plant Breeding and Seed Science, 2008)
The historical and contemporary population genotypic structure of pea blight pathogens, A.pinodes and P.pinodella was determined on temporal and spatial scale by using vegetative incompatibility system as phenotypic genetic marker. It has been indicated that since new 1976 VCG genotypes had been introduced into contemporary population in Poland. Significantly genotypic difference was found among old historical subpopulations sampled from different pea cultivars that were grown in three regions of Poland and historical subpopulations sampled from resistance nurseries artificially infested and long – term monocultures of pea. The difference between historical and contemporary populations also was significant indicating the Occurrence of two distinct populations of A.pinodes and P.pinodella during 1975 – 2004 period...